Innovative Human Resource Management Strategies During the Covid-19 Pandemic: Telecommuting Practice - Lisongwei, Lisongwei (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The purpose of this study is to analysis what is human resources management strategies during the covid-19 pandemic at PT Pengembangan Industri Logam. This study using qualitative research with 6 participants to make mini model. Mini-model theory was obtained that displays seven (7) latent variables that determine the success of human resource management strategies during covid-19 Mini Model Theory which are in the form of work from home, productivity and efficiency, information technology, work-life balance, communication, work facility and performance evaluation. Information technology and communication negatively affects human resources management strategies because of signal constraints experienced by employees when doing work at home. It also has an impact on work that cannot be interrupted on time and communication that is hampered.